First record of the genus Cladonema (medusae and polyps) in Colombia - Cedeño-Posso, Cristina (Zootaxa, 2014)
Knowledge about the cnidarian class Hydrozoa in Colombia is very limited because there are few investigators researching this group. Studies on hydropolyps from the Colombian Caribbean include Wedler (1973, 1975), Bandel & Wedler (1987), Florez (1983) and Posada et al. (2010), whereas those focused on hydromedusae are Moncaleano-Niño (1976), who documented 20 genera and Dominguez (2002), who documented 6 families and 5 genera. On the Pacific coast, only Lopez and Baldrich (2010) have published on 12 families and 13 genera based on observations of hydromedusae. This paper reports for the first time in the Colombian Caribbean the hydrozoan genus Cladonema based on a colony of polyps and their medusae.